Ứng dụng công nghệ thông tin tại Thư viện Khoa học Xã hội: thành công và tồn tại - Nguyễn, Lê Phương Hoài (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article introduces the overall process of applying information technology in implementing information-library activities at the Library of Academy of Social Sciences. It also introduces the achievements and limitations of the application as well as proposing solutions to mitigate the limitations.